FRI0165 RISK OF CKD IN MEMBRANOUS AND PROLIFERATIVE LUPUS NEPHRITIS - ANALYSIS OF A NATIONWIDE MULTICENTRE COHORT. (2nd June 2020) - Farinha, F.; Barreira, S. C.; Couto, M.; Cunha, M.; Fonseca, D.; Freitas, R.; Inês, L.; Luis, M.; Macieira, C.; Prata, A. R.; Rodrigues, J.; Santos, B.; et al.
Abstract : Background: Lupus nephritis (LN) is one of the most severe manifestations of Systemic Lupus Erythematosus. Objectives: 1) To compare proliferative (PLN), membranous (MLN) and mixed LN regarding clinical and laboratory presentation. 2) To investigate predictors of progression to chronic kidney disease (CKD). Methods: Multicentre observational study, with retrospective analysis of a prospective cohort, using data from the Portuguese registry of rheumatic diseases – Reuma.pt. Patients with biopsy-proven PLN, MLN and mixed LN were included. Groups were compared using Pearson's Chi-Square for categorical variables and One-Way ANOVA or Kruskal-Wallis for numerical variables. COX regression analysis was used to investigate predictors of CKD (defined as estimated glomerular filtration rate [eGFR] lower than 60 mL/min/1.73m 2 for at least 3 months) and Kaplan-Meier curves were drawn. Results: 236 patients were included. Median follow-up was 8 years (IQR 11; maximum 35 years). As seen in table 1, the level of proteinuria did not differ between groups; however, MLN patients presented with significantly lower serum creatinine. Levels of complement C3 and C4 were reduced in PLN but normal in MLN patients, and there were fewer patients with positive anti-dsDNA antibodies in the MLN group (p<0.001). On univariable COX regression, mixed histology was associated with progression to CKD (HR 26 [95% CI 3 - 255], p 0.005) (figure 1 ), however, it lost significance after adjusting for eGFR. In fact, eGFR≤75 at one year after the renal biopsy (HR 21 [95% CI 7 - 65], p<0.001) was the strongest predictor of CKD, even after adjusting for hypertension or histology. Conclusion: Our results support previous findings from single-centre studies suggesting that MLN has a different serological profile than PLN, possibly reflecting different pathogenesis. Renal function at one year predicts long-term outcome in LN. Disclosure of Interests: Filipa Farinha: None declared, Sofia C Barreira: None declared, Maura Couto: None declared, Margarida Cunha: None declared, Diogo Fonseca: None declared, Raquel Freitas: None declared, Luís Inês: None declared, Mariana Luis: None declared, Carla Macieira: None declared, Ana Rita Prata: None declared, Joana Rodrigues: None declared, Bernardo Santos: None declared, Rita Pinheiro Torres: None declared, Ruth J. Pepper: None declared, Anisur Rahman: None declared, Maria Jose Santos Speakers bureau: Novartis and Pfizer